Is there a place for women in the theology of the Psalms? PART II : self-expression and the 'I' in the Ancient Hebrew Psalter - Efthimiadis-Keith, Helen (Old Testament Essays, 2004)
This paper is Part II of a research project that investigates the place of women in the theology of the ancient Hebrew Psalter. Whereas Part I attempted to determine the nature of this 'place' from the perspective of the female imagery contained in the book (OTE 12/1, 35-56), Part II endeavours to do so from the perspective of the 'I'. More specifically, Part II deals with the self-expression of the 'I', its identity and the possibility of female authorship for at least some of the Psalms. It also integrates the findings of a questionnaire that was recently distributed amongst men and women in order to test their responses to the Psalms.
free